The EFFECT OF CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE WITH THE EFFECT PROFIT MANAGEMENT MODERATION (Empirical Study on Energy Sector Companies on the IDX Period 2021 -2023) - Fitri, Niken; Hadi Sucipto (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) on the financial performance of Energy Sector Companies listed on the IDX for the 2021-2023 Period and evaluate the moderating effect of earnings management on the relationship between CSR and financial performance of Energy Sector Companies listed on the IDX for the 2021-2023 Period. The population of this study is energy sector companies whose shares are listed on the Indonesia Stock Exchange (IDX) in 2021-2023 and the research sample is 10 companies. Using processed with SPSS. The results of the study show that CSR has a significant positive effect on financial performance in Energy Sector companies listed on the IDX for the 2021-2023 Period. Earnings management is unable to moderate the relationship between CSR and financial performance in Energy Sector companies listed on the IDX for the 2021-2023 Period.